EFFECT OF LEGUMES LIVING MULCHES ON SOIL MOISTURE, WEED INFESTATION, GROWTH AND YIELD OF MAIZE (ZEA MAYS L.) DURING DRY SEASON - Htwe, Ei Mon; Zar, Thu (AGPE THE ROYAL GONDWANA RESEARCH JOURNAL OF HISTORY, SCIENCE, ECONOMIC, POLITICAL AND SOCIAL SCIENCE, 2024)
The experiment was conducted at the field of Department of Agronomy, Yezin Agricultural University, Myanmar to study the effect of green gram and cowpea living mulches on soil moisture, weed infestation, growth, and yield of maize, and to select the suitable living mulch in maize cultivation during dry season. The experiment was conducted by using randomized complete block design (RCB) with three replications. A total of seven treatments were comprised of control (no mulch) (T1), maize: green gram (1:1) (T2), maize: green gram (1:2) (T3), maize: green gram (1:3) (T4), maize: cowpea (1:1) (T5), maize: cowpea (1:2) (T6) and maize: cowpea (1:3) (T7). Soil moisture content and weed infestation were significantly different among the treatments. The maximum weed infestation was recorded from T1 (no mulch) at all sampling times. The minimum weed infestation was observed from maize: cowpea (1:2) (T6) followed by maize: cowpea (1:3) (T7) at 20 DAS and 80 DAS. At 40 DAS and 60 DAS, the minimum weed infestation was found in T7 followed by T6. In addition, the maximum weed control efficiency was found in T6 at 20 DAS and T7 followed by T6 at 40 DAS. The highest leaf area index was attained from T6 at maximum vegetative growth stage. The maximum crop growth rate was observed from maize: green gram (1:2) (T3) and maize: green gram (1:3) (T4) from vegetative growth stage to grain filling stage. However, the maximum grain yield was recorded from maize: cowpea ((1:2) (T6). According to the results, maize: cowpea ((1:2) (T6) is suitable for maize cultivation during dry season of the study area.